Meta-Bank: Pioneering the Metaverzation of Financial Services - Hu, Bing (Journal of Theory and Practice of Management Science, 2024)
Meta-Bank is at the forefront of transforming financial services through the innovative process of metaverzation. This article delves into how Meta-Bank integrates cutting-edge technologies and collaborates with industry leaders like Meta, Nvidia, OpenAI, Tesla, and a major US bank to create an immersive and efficient financial ecosystem. Key areas of focus include the adoption of virtual reality (VR), artificial intelligence (AI), and autonomous technologies, as well as the exploration of business opportunities in NFTs and cryptocurrency. By bridging the gap between traditional financial services and the emerging virtual landscape, Meta-Bank aims to enhance convenience, security, and accessibility for users, setting a new standard for financial interactions in the metaverse. The future prospects of Meta-Bank highlight its ongoing commitment to innovation and practical application, ensuring its pivotal role in the evolving financial landscape.